A general strategy to inhibit serine protease by targeting its autolysis loop. Issue 2 (8th January 2021) - Jiang, Longguang; Yuan, Cai; Huang, Mingdong
Abstract: Serine proteases are a large family of enzymes critical for multiple physiological processes, and proven diagnostic and therapeutic targets in several clinical indications. The high similarity of active sites among different serine proteases posts a challenge to reach high selectivity for inhibitors of serine proteases targeting at the active site. Here, we demonstrated that one particular surface loop on serine proteases (autolysis loop) can be used to regulate their catalytic activity, through surveying the recent works including ours, and such an approach can reach high specificity. The autolysis loop is highly variable among different serine proteases, explaining the high specificity of inhibitors targeting the autolysis loop. We also outline the structural origin that links the perturbation of the autolysis loop and the inhibition of protease activity. Thus, the autolysis loop appears to be a highly sensitive allosteric site and can be used as a general handle to develop pharmacological agents to intervene with the activities of serine proteases in, eg, blood coagulation.